Large Diversity and Original Structures of Acyl-Homoserine Lactones in Strain MOLA 401, a Marine Rhodobacteraceae Bacterium - Doberva, Margot; Stien, Didier; Sorres, Jonathan; Hue, Nathalie; Sanchez-Ferandin, Sophie; Eparvier, Véronique; Ferandin, Yoan; Lebaron, Philippe; Lami, Raphaël (Frontiers in Microbiology, 2017)
Quorum sensing (QS) is a density-dependent mechanism allowing bacteria to synchronize their physiological activities, mediated by a wide range of signaling molecules including N-acyl-homoserine lactones (AHLs). Production of AHL has been identified in various marine strains of Proteobacteria. However, the chemical diversity of these molecules still needs to be further explored. In this study, we examined the diversity of AHLs produced by strain MOLA 401, a marine Alphaproteobacterium that belongs to the ubiquitous Rhodobacteraceae family. We combined an original biosensors-based guided screening of extract microfractions with liquid chromatography coupled to mass spectrometry (MS), High Resolution MS/MS and Nuclear Magnetic Resonance (NMR). This approach revealed the unsuspected capacity of a single Rhodobacteraceae strain to synthesize 20 different compounds, which are most likely AHLs. Also, some of these AHLs possessed original features that have never been previously observed, including long (up to 19 carbons) and poly-hydroxylated acyl side chains, revealing new molecular adaptations of QS to planktonic life and a larger molecular diversity than expected of molecules involved in cell-cell signaling within a single strain.